Study of deserted construction projects in Malaysia - Nazratul Izzana, Ishak (2015)
One of the most significant sectors that contribute to Malaysia's economic growth is the construction industries and it supplies a great deal of opportunities to whom involved to flourish in this sector. Even so, deserted construction project (DCP) in Malaysia is considered as one of the most usual and serious problems existing in construction industry nowadays. The desertion of construction projects has resulted in many adverse consequences to the economic system, society and towards environment. This study suggests to identify the reasons that contribute to this problem in order to bring down the negative impact of DCP, and try to determine how to prevent DCP from happen again. Respondents selected for this study were from Class B Contractors to Class A Contractors in peninsular Malaysia that were listed in the current Construction Industry Development Board(CIDB) directory. 170 sets of questionnaires were distributed and 122 questionnaires were returned for further analyses. Foremost, the issues skirting the problem and existing literature on the reasons of DCP are reexamined. Besides, potential reasons of the DCP are also reviewed and summed up into 41 items to be rated in an industry wide questionnaire survey. An open-ended question were also included in the questionnaire to resolve DCP. Afterward, a series of ten semi-structured interviews were conducted to getting detailed opinions from experienced players in the industry concerning the reasons of DCP and how to solve the problems. The interviewees include architects, developers, property consultants, the honorary secretary general of the National House Buyers Association etc. to ensure a comprehensive view was obtained. Quantitative analyses include ranking of the 41 possible reasons of DCP with Spearman‟s ranking correlation between different groups of respondents, and factor analysis with Cronbach‟s α reliability analysis. Qualitative analyses include organizing the results of the open ended question and results of the semi-structured interviews. The discussions included interpret basic factors got from factor analysis based on the outcomes of the qualitative. The outcomes indicated that the owner is mainly responsible for DCP (i.e. cash flow problems, incompetence, siphoning out of money, etc.), followed by the role of government regulations. A risk management expert system module within BIM, a middle ground solution between the sell-then-build and build-then-sell schemes, and others are proposed